Titanium as a Possible Modifier of Inflammation Around Dental Implants - Kandaswamy, Eswar; Sakulpaptong, Wichurat; Guo, Xiaohan; Ni, Ai; Powell, Heather M; Tatakis, Dimitris N; Leblebicioglu, Binnaz (The International journal of oral and maxillofacial implants, 2022)
The exact etiopathogenesis of peri-implant diseases remains unclear. While significant information on molecular markers is available, studies on biomarkers related to possible biocorrosion are sparse. This study aimed to evaluate periimplant crevicular fluid (PICF) for possible titanium (Ti) contamination and explore associations between clinical findings, inflammatory mediators, and Ti levels. Patients with implant-supported restoration (≥ 1 year in function) were recruited for this cross-sectional study. Demographics, systemic, and periodontal health history were recorded. Clinical evaluations were conducted to reach peri-implant/periodontal diagnoses and grade severity of peri-implant soft tissue inflammation. Crevicular fluid (CF) was collected from both implants and adjacent teeth (PICF, gingival crevicular fluid [GCF]) and analyzed for Ti (inductively coupled plasma mass spectrometry) and inflammatory mediators (V-plex assays). Multiple regression analysis with a linear mixed effect model was used to analyze possible associations between clinical diagnosis, PICF/GCF cytokine, and Ti concentrations. Seventy-seven patients (aged 62 ± 2 years; 39 male) with 117 implants (9 ± 1 years in function) were recruited. Diabetes, positive periodontitis history, and current/former smoking were reported by 8%, 39%, and 39% of subjects, respectively. Seventy-nine implant sites (63 patients) were included in CF cytokine analysis, and 45 of these sites (42 patients) were paired with Ti analysis. Statistically significant increases from health to disease were noted in log-transformed PICF concentrations of IL-1β, IL-6, IL-10, and INF-γ (P ≤ .05). Also, statistically significant increases from health to severe clinical inflammation were detected in log-transformed PICF concentrations of IL-8, IL-13, and TNF-α (P ≤ .05). Ti was detected in the majority (82%) of PICF and GCF samples. There was no statistically significant difference in log-transformed Ti concentration based on disease status. However, log-transformed Ti concentration was positively correlated to IL-1β, IL-2, IL-4, IL-8, IL-13, and INF-γ concentrations when data were adjusted for site-specific health (P ≤ .05). Ti was detectable in PICF and adjacent GCF, even in health. Specific inflammatory mediator concentrations were increased in peri-implant disease and significantly associated with Ti concentrations, even when data were adjusted for peri-implant health status. Increased GCF inflammatory mediator concentrations were also associated with increased Ti concentrations. Ti effects on peri-implant as well as periodontal tissues require additional longitudinal investigations.